2018
DOI: 10.1542/peds.2017-2127
|View full text |Cite
|
Sign up to set email alerts
|

Parental Adverse Childhood Experiences and Resilience on Coping After Discharge

Abstract: More parental adversity and less resilience are associated with parental coping difficulties after discharge, representing potentially important levers for transition-focused interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 34 publications
3
31
0
1
Order By: Relevance
“…Overall, parental ACEs seem to have a transgenerational relationship with developmental problems in their children [ 80 , 81 , 82 , 83 ]. More parental ACEs and less resilience have been found to be associated with parental coping difficulties [ 84 ]. A study by Folger and colleagues showed that parental ACEs can negatively impact child development at 2 years of age on the following domains: communication, problem solving and personal- social- and motor skills [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, parental ACEs seem to have a transgenerational relationship with developmental problems in their children [ 80 , 81 , 82 , 83 ]. More parental ACEs and less resilience have been found to be associated with parental coping difficulties [ 84 ]. A study by Folger and colleagues showed that parental ACEs can negatively impact child development at 2 years of age on the following domains: communication, problem solving and personal- social- and motor skills [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other two intervention‐based studies assessed the influence of interventions targeted at promoting general rehabilitation or health outcomes and well‐being of the study sample. Shah et al () used the BRS to assess the influence of a nurse‐led transitional home visit on parents of children with chronic conditions after their children were discharged from the hospital. No significant difference in the level of resiliency was found between parents who received the home visit intervention and those who did not receive the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 41 studies that we identified, only five were intervention studies that assessed resiliency as outcome variables. While aiming at measuring the impacts of resiliency‐related interventions, these five intervention studies employed assessment tools designed to explain intrapsychic and contextual protective factors available to the study participants—CD‐RISC (Yi‐Fraizer et al, ; Baron Nelson et al, ), RS (Lee at al., ; Pandya, ), or BRS (Shah et al, ), respectively—rather than one's capacity to flexibly adapt to changing life circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations